Satirizing Christianity in Lucian’s Peregrinus and Achilles Tatius’ Leucippe and Clitophon - Kanavou, Nikoletta (Novum Testamentum, 2025)
This article focuses on early pagan references to the Christian movement with a satirical spirit; it revisits Lucian’s most extensive Christian-related satire, The Passing of Peregrinus—a biography that ridicules the Cynic philosopher Peregrinus, who is mainly famous for his self-immolation in Olympia at the games of AD 165, after a tangled career that included a significant brush with Christianity—and suggests the novel of Achilles Tatius, The Adventures of Leucippe and Clitophon, as a further example of probable satire at the expense of the Christians. It is argued that the apparent construction of satire of Christianity in the Lucianic piece strengthens the case for seeing relevant satire in Achilles Tatius too, but the rather more implicit nature of Achilles Tatius’ satire has guaranteed him a more positive Christian reception than Lucian’s.